2011
DOI: 10.1007/s11033-011-0841-z
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and expression of squalene synthase and 2,3-oxidosqualene cyclase genes in persimmon (Diospyros kaki L.) fruits

Abstract: Oleanolic acid (OA) and ursolic acid (UA) are the main triterpene acids in persimmon fruit, and squalene synthase and 2,3-oxidosqualene cyclases are important enzymes in pentacyclic triterpene biosynthesis. In order to study their relationship, DkSQS and DkOSC were cloned from persimmon fruits in the present study. The full-length cDNA of DkSQS was 1647 bp, containing an open reading frame (ORF) of 1245 bp that encoded a peptide of 415 amino acids (AA). The 3'-end of DkOSC cDNA fragment contained 522 bp, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
2
3
0
Order By: Relevance
“…SgSQS has two transmembrane domains in the C-terminal region, which is consistent with the reported presence of SQSs in the ER membrane13, 14. SQS genes have been identified in many organisms, including algae 15 , yeast, animals and plants 16 .…”
Section: Discussionsupporting
confidence: 90%
“…SgSQS has two transmembrane domains in the C-terminal region, which is consistent with the reported presence of SQSs in the ER membrane13, 14. SQS genes have been identified in many organisms, including algae 15 , yeast, animals and plants 16 .…”
Section: Discussionsupporting
confidence: 90%
“…In the case of other fruits, a diminution of SQS transcript levels has been described during the development and ripening of persimmon fruit. 47 In olive, the higher expression level detected for OeSQS2 in 'Picual' mesocarp is in line with the higher squalene content observed for this cultivar compared to 'Arbequina'. This result, together with the fact that this gene showed the highest transcript level of olive SQS genes in the mesocarp tissue, indicates that OeSQS2 seems to be the gene that mainly contributes to the biosynthesis of squalene in the olive mesocarp.…”
Section: Variability Of the Squalene Content In An Olivesupporting
confidence: 56%
“…All of these data point out that in olive fruit, the expression of SQS genes seems to be temporally regulated during the developmental and ripening period. In the case of other fruits, a diminution of SQS transcript levels has been described during the development and ripening of persimmon fruit …”
Section: Resultsmentioning
confidence: 99%
“…Quantitative analysis of the triterpenoid content in neem (Azadirachta indica) indicated that there was tissue-specific variation in terms of abundance (Pandreka et al, 2015). Oleanolic acid (OA) and ursolic acid (UA), the main triterpene acids in persimmon fruit, changed during fruit development (Zhou et al, 2012). Limonin and nomilin, as the predominant limonoids in a group of chemically related triterpene derivatives in the Rutaceae and Meliaceae plant families, increased at first and then gradually decreased in some citrus species during growth and maturation when the limomoid UDP-glucosyltransferase regulated the conversion of limonoid to glucoside (Kita et al, 2000).…”
Section: Discussionmentioning
confidence: 99%